Dibenzo[def, p]chrysene transplacental carcinogenesis in wild‐type, Cyp1b1 knockout, and CYP1B1 humanized mice. Issue 1 (17th March 2016) - Madeen, Erin P.; Löhr, Christiane V.; You, Hannah; Siddens, Lisbeth K.; Krueger, Sharon K.; Dashwood, Roderick H.; Gonzalez, Frank J.; Baird, William M.; Ho, Emily; Bramer, Lisa; Waters, Katrina M.; Williams, David E.
Abstract : The cytochrome P450 (CYP) 1 family is active toward numerous environmental pollutants, including polycyclic aromatic hydrocarbons (PAHs). Utilizing a mouse model, null for Cyp1b1 and expressing human CYP1B1, we tested the hypothesis that hCYP1B1 is important for dibenzo[ def, p ]chrysene (DBC) transplacental carcinogenesis. Wild‐type m Cyp1b1, transgenic h CYP1B1 (m Cyp1b1 null background), and m Cyp1b1 null mice were assessed. Each litter had an equal number of siblings with Ahr b‐1/d and Ahr d/d alleles. Pregnant mice were dosed (gavage) on gestation day 17 with 6.5 or 12 mg/kg of DBC or corn oil. At 10 months of age, mortality, general health, lymphoid disease and lung tumor incidence, and multiplicity were assessed. h CYP1B1 genotype did not impact lung tumor multiplicity, but tended to enhance incidence compared to Cyp1b1 wild‐type mice ( P = 0.07). As with Cyp1b1 in wild‐type mice, constitutive hCYP1B1 protein is non‐detectable in liver but was induced with 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin. Wild‐type mice were 59% more likely to succumb to T‐cell Acute Lymphoblastic Leukemia (T‐ALL). Unlike an earlier examination of the Ahr genotype in this model (Yu et al., Cancer Res, 2006;66:755–762), but in agreement with a more recent study (Shorey et al., Toxicol Appl Pharmacol, 2013;270:60–69), this genotype was not associated with lung tumor incidence, multiplicity, or mortality. Sex was not significant with respect to lung tumor incidence or mortality but males exhibited significantly greater multiplicity. Lung tumor incidence was greater in m Cyp1b1 nulls compared to wild‐type mice. To our knowledge, this is the first application of a humanized mouse model in transplacental carcinogenesis. © 2016 Wiley Periodicals, Inc.